Cell Envelope and Shape of Escherichia coli K12 - Henning, Ulf (1973)
Rod-shaped “ghosts” that are free of murein have been isolated from E. coli. The shape of these “ghosts” is maintained by a unit membrane soluble in sodium dodecyl sulfate. Ghosts consist of about 20-30% phospholipid (almost exclusively phosphatidylethanolamine) and 50-60% protein; a large fraction of the remaining material is lipopolysaccharide. Sodium dodecyl sulfate-gel electrophoresis reveals 4-5 different bands corresponding to molecular weights between 10,000 and 40,000. Treatment of ghosts with Pronase reduces this number to 3, and the rod shape still is not lost. Results of treatment of ghosts with a crude extract from Dictyostelium discoideum have supplied tentative evidence that at least one of these proteins is involved in the maintenance of rod shape. It does not appear too unlikely that these polypeptide chains are the final products of the genetic information specifying cellular shape.